A comparative study of side-chain-type poly(ether ether ketone) anion exchange membrane functionalized with different hetero-cycloaliphatic quaternary ammonium groups. Issue 14 (11th March 2019) - Yao, Dan; Wei, Tonghui; Shang, Lichao; Na, Hui; Zhao, Chengji
Abstract : Anion exchange membranes based on side-chain-type quarternized poly(ether ether ketone)s QPEEKs containing different hetero-cycloaliphatic quaternary ammonium groups were prepared via polycondensation, bromomethylation and quaternization. Abstract : Anion exchange membranes based on side-chain-type quarternized poly(ether ether ketone)s (QPEEKs), containing different hetero-cycloaliphatic quaternary ammonium groups, were prepared via a multi-step procedure, including polycondensation with a monomer containing pendant methylphenyl groups, bromomethylation, and followed by quaternization with 1-methylpyrrolidine (MPY), 1-methylpiperidine (MPRD), 1-methylimidazole (MIDZ) and N -methyl morpholine (MMPH), respectively. The properties of these membranes were then compared with the properties of conventional quarternized poly(ether ether ketone)s containing benzyltrimethylammonium (QPEEK-TMA). Model compounds, QMPY, QMPRD, QMIDZ and QMMPH, were synthesized and used to quantitatively compare the alkaline stability of hetero-cycloaliphatic quaternary ammonium groups using 1 H NMR. The results of this study indicated that the alkaline stability of all these model compounds is in the order of QMPY > QMPRD > QTMA > QMIDZ > QMMPH. These QPEEKs membranes display superior thermal, dimensional and mechanical stability. QPEEK-TMA, QPEEK-MPY and QPEEK-MPRD exhibit higher hydroxide conductivities and lower activation energies than QPEEK-MIDZ and QPEEK-MMPH. Furthermore, after exposure to 1 M NaOH at 60 °C for 24 days, QPEEK-MPY and QPEEK-MPRD demonstrated a loss in hydroxide conductivity of 28.5% and 33.4%, respectively. Both values were lower than that of QPEEK-TMA (37.7%). Therefore, among these side-chain-type QPEEKs membranes, QPEEK-MPY and QPEEK-MPRD, containing benzylmethylpyrrolidinium and benzylmethylpiperidinium as cation head-groups, are promising AEM materials for fuel cell construction.